Association between disease activity and HALP score in ankylosing spondylitis patients - Cüre, Osman (The European Research Journal, 2025)
Objective: The goal of this research was to assess HALP score (Hemoglobin, Albumin, Lymphocyte, Platelet) as a potential indicator of disease activity among patients with Ankylosing Spondylitis (AS). Methods: Data from 260 individuals (130 AS patients and 130 healthy controls) were retrospectively reviewed. Clinical and demographic information was collected, and the AS group was divided into remission and active disease subgroups for comparison. Results: In contrast to the group of healthy controls, AS patients had a lower HALP score (P